The isolation and characterization of bacteria exhibiting deinking activity from regions in Sylhet - Alam, Afia Salsabil; Zanzabil, Khwaja Zohura; Mahmood, Maiesha Samiha (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.